Serum cystatin C is a sensitive early marker for changes in the glomerular filtration rate in patients undergoing laparoscopic surgery - Moreira E Lima, Rodrigo; Navarro, Lais Helena Camacho; Nakamura, Giane; Solanki, Daneshvari R.; Castiglia, Yara Marcondes Machado [UNESP]; Vianna, Pedro Thadeu Galvão [UNESP]; Ganem, Eliana Marisa [UNESP] (Universidade de São Paulo (USP), Faculdade de Medicina, 2014)
OBJECTIVE: Pneumoperitoneum during laparoscopy results in transient oliguria and decreased glomerular filtration and renal blood flow. The presence of oliguria and elevated serum creatinine is suggestive of acute renal injury. Serum cystatin C has been described as a new marker for the detection of this type of injury. In this study, our aim was to compare the glomerular filtration rate estimated using cystatin C levels with the rate estimated using serum creatinine in patients with normal renal function who were undergoing laparoscopic surgery. METHODS: In total, 41 patients undergoing laparoscopic cholecystectomy or hiatoplasty were recruited for the study. Blood samples were collected at three time intervals: first, before intubation (T1); second, 30 minutes after the establishment of pneumoperitoneum (T2); and third, 30 minutes after deflation of the pneumoperitoneum (T3). These blood samples were then analyzed for serum cystatin C, creatinine, and vasopressin. The Larsson formula was used to calculate the glomerular filtration rate based on the serum cystatin C levels, and the Cockcroft-Gault formula was used to calculate the glomerular filtration rate according to the serum creatinine levels. RESULTS: Serum cystatin C levels increased during the study (T1 = T2<T3; p<0.05), whereas serum creatinine levels decreased (T1 = T2>T3; p<0.05). The calculated eGlomerular filtration rate-Larsson decreased, whereas the eGlomerular filtration rate-Cockcroft-Gault increased. There was no correlation between cystatin C and serum creatinine. Additionally, Pearson's analysis showed a better correlation between serum cystatin C and the eGlomerular filtration rate than between serum creatinine and the eGlomerular filtration rate. CONCLUSION: This study demonstrates that serum cystatin C is a more sensitive indicator of changes in the glomerular filtration rate than serum creatinine is in patients with normal renal function who are undergoing laparoscopic procedures.
Keywords: Cystatin C; Creatinine; Glomerular Filtration Rate; Laparoscopy